Case report: Type I diastematomyelia with breast abnormalities and clubfoot - Hao, Shenshen; Yue, Zenan; Yu, Xin; Gao, Zhenfu; Li, Hongke; Liu, Shuai; Dong, Shengli (Frontiers in Surgery, 2022)
Background: Diastematomyelia is a rare congenital spinal cord malformation, classified as type I or type II, with over half of the cases considered type I. However, type I diastematomyelia with breast abnormality and clubfoot is extremely rare in clinical practice. Case presentation: We admitted an 18-year-old female patient with type I diastematomyelia with breast abnormalities and clubfoot. She was underwent surgical treatment. After the surgical removal of the pressure-causing bone structure, the weakness of the right lower limb was significantly relieved. During the 22-month follow-up, there was no complication and no recurrence. Conclusion: Surgical removal of the pressure-causing bone structure can relieve symptoms in the lower limbs. However, further research is warranted to explore the breast abnormalities in patients with diastematomyelia.